A case study of lean, sustainable manufacturing - Geoff Miller; Janice Pawloski; Charles R. Standridge (Journal of Industrial Engineering and Management (JIEM), 2010)
A small furniture production company has integrated lean tools and sustainability concepts with discrete event simulation modeling and analysis as well as mathematical optimization to make a positive impact on the environment, society and its own financial success. The principles of lean manufacturing that aid in the elimination of waste have helped the company meet ever increasing customer demands while preserving valuable resources for future generations. The implementation of lean and sustainable manufacturing was aided by the use of discrete event simulation and optimization to overcome deficits in lean's traditional implementation strategies. Lean and green manufacturing can have a more significant, positive impact on multiple measures of operational performance when implemented concurrently rather than separately. These ideas are demonstrated by three applications.
Keywords: 650; lean manufacturing; green manufacturing; case-study; discrete event simulation; optimization